THE INFLUENCE OF APPLICATION OF GAME BASED PASSING TRAINING MODELS ON SENIOR HIGH SCHOOL STUDENTS PASSING SKILL - Deni Mudian; Moch. Asmawi; Taufik Rihatno (Program Pascasarjana Universitas Negeri Jakarta, 2020)
Passing skill done by SMP IT Alamy students still too fast and inaccurate, which made difficult for another football player to take the ball. The aim of this study to investigate the effect of application game-based model of passing football training on IT ‘Alamy junior high school. This type of research is an experiment with the design of